MAINTAINING THE IDENTITY OF BILINGUAL INDIVIDUALS IN MULTICULTURAL/MULTILINGUAL SETTINGS - Ika Kana Trisnawati (Englisia: Journal of Language, Education, and Humanities, 2017)
This paper discusses the ways bilingual people are able to maintain their identity within any multicultural and multilingual environment. As today’s societies have shown to have more people with varied language/cultural backgrounds, it is interesting to learn how the bilinguals understand and identify themselves despite living in a totally different environment. Data in this paper came from a number of multicultural/multilingual settings for comparison purposes. Findings showed that there have been three major factors contributing to maintain the bilinguals’ identity in a diverse environment including language, family, and peer interaction.